2008
DOI: 10.1007/s00427-008-0249-5
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of linkage and evolution of developmental function within the Tbx2/3/4/5 subfamily of T-box genes: implications for the origin of vertebrate limbs

Abstract: T-box genes encode a family of DNA-binding transcription factors implicated in numerous developmental processes in all metazoans. The Tbx2/3/4/5 subfamily genes are especially interesting because of their key roles in the evolution of vertebrate appendages, eyes, and the heart, and, like the Hox genes, the longevity of their chromosomal linkage. A BAC library derived from the single male amphioxus (Branchiostoma floridae) used to sequence the amphioxus genome was screened for AmphiTbx2/3 and AmphiTbx4/5, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 73 publications
(70 reference statements)
2
56
0
1
Order By: Relevance
“…In transgenic analysis, constructs containing fragments of the mouse Tbx5 and Tbx4 genomic regions are able to drive gene expression in the forelimb-and hindlimbforming regions of the LPM while, in contrast, the amphiTbx4/5 genomic locus appears to lack the regulatory modules enabling expression in the LPM. In accordance with broadly accepted evolutionary models, these results suggest that changes at the level of the regulation of Tbx5 and Tbx4expression, rather than the generation of novel protein function, was necessary for the acquisition of paired appendages during vertebrate evolution (Horton et al, 2008;Minguillon et al, 2009). …”
Section: Limb Forming Capacity Of Tbx4 and Tbx5 Is Evolutionarily Ancsupporting
confidence: 85%
“…In transgenic analysis, constructs containing fragments of the mouse Tbx5 and Tbx4 genomic regions are able to drive gene expression in the forelimb-and hindlimbforming regions of the LPM while, in contrast, the amphiTbx4/5 genomic locus appears to lack the regulatory modules enabling expression in the LPM. In accordance with broadly accepted evolutionary models, these results suggest that changes at the level of the regulation of Tbx5 and Tbx4expression, rather than the generation of novel protein function, was necessary for the acquisition of paired appendages during vertebrate evolution (Horton et al, 2008;Minguillon et al, 2009). …”
Section: Limb Forming Capacity Of Tbx4 and Tbx5 Is Evolutionarily Ancsupporting
confidence: 85%
“…It is suggested essential cis-regulatory elements (located in flaking or intragenic regions) are likely to be found in close vicinity to these loci. 52 Minguillon et al 53 showed that changes at the regulatory level of Tbx4 and Tbx5 expression were necessary for the development of paired appendages during vertebrate evolution, rather than the generation of novel protein function. We speculate that the atypical HOS phenotype seen in this family could be due to a number of possible underlying pathogenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The full-length sequence of the AmphiTbx4/5 gene was deduced from the sequence of the CH302 78M15 BAC (17). We used RT-PCR on a 56-h embryonic cDNA sample to obtain the putative full-length coding region.…”
Section: Methodsmentioning
confidence: 99%